Good Relationships, Good Performance: The Mediating Role of Psychological Capital – A Three-Wave Study Among Students - Carmona-Halty, Marcos; Schaufeli, Wilmar B.; Salanova, Marisa (Frontiers in Psychology, 2019)
Academic Psychological Capital, or PsyCap, –a set of positive psychological resources encompassing hope, efficacy, resilience, and optimism– has begun to gain attention in academia, showing positive relationships with desirable academic outcomes. However, studies in the field have paid limited attention to the social factors that may increase PsyCap and therefore may lead to positive outcomes. In the present study –integrating self–determination theory (SDT) and conservation of resources (COR) theory– we examine whether academic PsyCap mediates between teacher–student relationships (TSR) and academic performance (AP) as assessed by student’s GPA, using a three–wave longitudinal design. Through structural equation modelling (SEM), as expected, a statistically significant indirect effect was found between TSR and AP via academic PsyCap. Theoretical and practical implications of the results are discussed, strengths and weaknesses are mentioned, and future research directions are proposed.